Validation of the intercultural sensitivity scale in the Spanish context - Gómez Yepes, Talía; Etchezahar, Edgardo; Albalá Genol, Miguel Ángel; Maldonado Rico, Antonio (Frontiers in Education, 2023)
The aim of this study was to validate the Intercultural Sensitivity Inventory (ISI) in the Spanish context, testing the five, four, and three-dimensional models of the construct and examining its relationship with other psychological variables. A Spanish sample of 872 participants aged between 18 and 80 years old (M = 52.50; SD = 17.41) was used. The main results indicated an adequate fit for the three correlated dimensions model (two of them include two dimensions of the original scale). In addition, an adequate fit for the original five-dimensional model or the theoretical four-dimensional alternative was not observed. Lastly, differences were observed based on the gender of the participants in the three dimensions of intercultural sensitivity, as well as in beliefs about the inclusion of immigrants in education and the rights of immigrants. The scope and limitations of the study are discussed, as well as the relationships with the observed psychosocial constructs.